2021
DOI: 10.1016/j.omtn.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Global RNA editing identification and characterization during human pluripotent-to-cardiomyocyte differentiation

Abstract: RNA editing is widely involved in stem cell differentiation and development; however, RNA editing events during human cardiomyocyte differentiation have not yet been characterized and elucidated. Here, we identified genome-wide RNA editing sites and systemically characterized their genomic distribution during four stages of human cardiomyocyte differentiation. It was found that the expression level of ADAR1 affected the global number of adenosine to inosine (A-to-I) editing sites but not the editing degree. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The expression level of ADAR1 was found to affect the global number of adenosine-to-inosine (A-to-I) editing sites but not the degree of editing. They found that these RNA editing sites are associated with several congenital and noncongenital heart diseases, thereby highlighting the link between cardiomyocyte differentiation and heart disease from an RNA editing perspective [ 96 ].…”
Section: Role Of Adar1 In Stem Cellsmentioning
confidence: 99%
“…The expression level of ADAR1 was found to affect the global number of adenosine-to-inosine (A-to-I) editing sites but not the degree of editing. They found that these RNA editing sites are associated with several congenital and noncongenital heart diseases, thereby highlighting the link between cardiomyocyte differentiation and heart disease from an RNA editing perspective [ 96 ].…”
Section: Role Of Adar1 In Stem Cellsmentioning
confidence: 99%
“…Focusing on RNA editing activity, a recent study identified several A-to-I editing events during human pluripotent stem cell-to-cardiomyocyte differentiation. Specifically, a minor (but significant) proportion of them were located within transcript coding sequences leading to amino acid changes [ 45 ], which may contribute to the generation of new proteins with distinct functions. In parallel with this, it has been reported that A-to-I editing within the mRNA 3′-untranslated region may represent a frequent event in many malignancies and can modify miRNA-binding motifs altering the miRNA putative targets.…”
Section: Rna Editing Cellular Transcriptome and Cancer Stem Cellsmentioning
confidence: 99%